A New Characterization of Normal Magnetic Biharmonic Particles in the Three Dimensional Heisenberg Space - Körpınar, Talat (AMER SCIENTIFIC PUBLISHERS, 2018)
In the present article, we define a new concept of normal magnetic particles by using biharmonic particles in Heisenberg space. We characterize the energy of normal magnetic particles and some Lorentz fields. Furthermore, we show that energy and magnetic flux density can be stated by Frenet fields in Heisenberg space.
Keywords: Biharmonic Particle; Bienergy; Heisenberg Space; Magnetic Field; Symmetries